Clinical and epidemiological profiles from a case series of 26 Brazilian CADASIL patients - Nogueira, Renata; Couto, Christian Marques; Oliveira, Pérola de; Martins, Bernardo José Alves Ferreira; Montanaro, Vinícius Viana Abreu (Arquivos de Neuro-Psiquiatria, 2023)
Background Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a genetic cause of ischemic stroke and the most common form of non-atherosclerotic stroke. Despite being the most prevalent vascular hereditary disease, clinical data regarding the Brazilian population are scarce. Considering that the Brazilian population has one of the most heterogeneous genetic constitutions in the world, knowledge about genetic and epidemiological profiles is mandatory. The present study aimed to elucidate the epidemiological and clinical features of CADASIL in Brazil. Methods We performed a case series study comprising 6 rehabilitation hospitals in Brazil and reported the clinical and epidemiological data from the medical records of patients admitted from 2002 to 2019 with genetic confirmation. Results We enrolled 26 (16 female) patients in whom mutations in exons 4 and 19 were the most common. The mean age at the onset of the disease was of 45 years. Ischemic stroke was the first cardinal symptom in 19 patients. Cognitive impairment, dementia, and psychiatric manifestations were detected in 17, 6, and 16 patients respectively. In total, 8 patients had recurrent migraines, with aura in 6 (75%) of them. White matter hyperintensities in the temporal lobe and the external capsule were found in 20 (91%) and 15 patients (68%) respectively. The median Fazekas score was of 2. Lacunar infarcts, microbleeds, and larger hemorrhages were observed in 18 (82%), 9, and 2 patients respectively. Conclusion The present is the most extensive series of Brazilian CADASIL patients published to date, and we have reported the first case of microbleeds in the spinal cord of a CADASIL patient. Most of our clinical and epidemiological data are in accordance with European cohorts, except for microbleeds and hemorrhagic strokes, for which rates fall in between those of European and Asian cohorts.
Keywords: CADASIL; Stroke; Epidemiology; Brazil; Receptor, Notch3